Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia - Souto, J.; Reverter-Gil, O. (Zootaxa, 2019)
During the late nineteenth and early twentieth centuries, a number of species of bryozoans were described in the genus Smittia Hincks, 1879 (a junior synonym of a dipteran genus). Jullien and/or Calvet named several species, mainly from the Bay of Biscay. Some of them have been re-examined in recent years and ascribed to Smittina Norman, 1903 and other genera. Five species, however, have remained unstudied. Here, type specimens of S. colletti, S. decipiens, S. fallax, S. gemmata, S. grimaldi and S. immersa—together with new specimens recently collected—are examined. The morphological study of all this material enabled the conclusion that only three species are involved. The synonymy of S. colletti with the senior species Smittina cervicornis is proposed; S. gemmata is transferred to the smittinid genus Raymondcia; and S. fallax, S. grimaldi and S. immersa, together with S. decipiens, are considered as junior subjective synonyms of Porella compressa.